2011
DOI: 10.1097/sla.0b013e318210f1f4
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and Cost Analysis of Sacral Nerve Modulation for Treating Urinary and/or Fecal Incontinence

Abstract: The SNM is a cost-effective treatment for urge urinary and/or fecal incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 0 publications
4
32
0
1
Order By: Relevance
“…Our results are comparable with results of SNM for urinary incontinence in general, with improved continence seen in two-thirds of patients after 2 years [25,26]. A retrospective series including 57 patients with double incontinence showed that urinary incontinence improved in 78% of the patients and faecal incontinence in 96% [27].…”
Section: Discussionsupporting
confidence: 75%
“…Our results are comparable with results of SNM for urinary incontinence in general, with improved continence seen in two-thirds of patients after 2 years [25,26]. A retrospective series including 57 patients with double incontinence showed that urinary incontinence improved in 78% of the patients and faecal incontinence in 96% [27].…”
Section: Discussionsupporting
confidence: 75%
“…20 Given the magnitude of these disorders, fecal and urinary incontinence place a significant burden on both society and health care systems. 22 The frequent association between fecal incontinence and functional urinary disorders can be explained by the fact that both types of incontinence share causative factors, including damage to the pelvic floor as a result of vaginal delivery, postoperative pelvic sequelae, common underlying motility disorders such as overactivity, and/or chronic straining to defecate. [23][24][25] The rationale for applying SNS to fecal incontinence was based on the clinical observations made by Matzel and colleagues 26 that SNS in urological patients showed effects on bowel function and anal continence.…”
Section: Discussionmentioning
confidence: 99%
“…There are currently six published cost-effectiveness analyses on the specialized treatment of OAB, looking at the national healthcare system's perspective in Spain and France [57,58], the societal perspective in the Netherlands [59 & ]; the payer's perspective in the USA [60], a provincial payers' perspective in Canada [61] and the societal perspective in the USA [62].…”
Section: Cost-effectiveness Of Onabotulinum Toxin a Versus Sacral Neumentioning
confidence: 99%